2015
DOI: 10.1016/j.pestbp.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference: Applications and advances in insect toxicology and insect pest management

Abstract: Since its discovery, RNA interference (RNAi) has revolutionized functional genomic studies due to its sequence-specific nature of post-transcriptional gene silencing. In this paper, we provide a comprehensive review of the recent literature and summarize the current knowledge and advances in the applications of RNAi technologies in the field of insect toxicology and insect pest management. Many recent studies have focused on identification and validation of the genes encoding insecticide target proteins, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 86 publications
1
90
0
5
Order By: Relevance
“…RNAi is high specificity, efficiency, stable, transmissible and hereditary; this characteristics make it a valuable tool to address various questions in insect toxicology, as well as may become an effective strategy for management of insect pests [83]. …”
Section: Resultsmentioning
confidence: 99%
“…RNAi is high specificity, efficiency, stable, transmissible and hereditary; this characteristics make it a valuable tool to address various questions in insect toxicology, as well as may become an effective strategy for management of insect pests [83]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that knockdown of ace1 genes led to increased sensitivity of insects to AChE insecticides (Revuelta et al 2009, 2011, Lu et al 2012b), and that silencing ace1 and/or ace2 impacted insect development (He et al 2012, Lu et al 2012b, Salim et al 2017). This suggests that these genes could be utilized for developing RNAi-based pest control strategies (Kim et al 2015). Prior to this study, ace genes had been isolated from a great number of insect species (Kim and Lee 2018), but little was known about ace genes in P. rapae .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, for example, studies demonstrated a high efficiency of the Bt soybean strain DAS-81419-2 (expressing two proteins) in the reduction of damage caused by A. gemmatalis, C. includens, H. virescens, and S. cosmioides during the vegetative and reproductive stages (Marques et al 2016). Recent studies have suggested the use of RNA interference as a promising alternative or complementary strategy for pest control and management (Asokan et al 2014;Kim et al 2015;Fishilevich et al 2016;Yu et al 2016;Ni et al 2017). …”
Section: Management Of Resistancementioning
confidence: 99%